Robot-assisted mobilisation in the intensive care unit: does it offer relief to mobilising specialists? A qualitative longitudinal study at a German university hospital - A. C. Mehler-Klamt; J. Huber; N. Koestler; A. Warmbein; I. Rathgeber; U. Fischer; I. Eberl (Discover Social Science and Health, 2024)
Abstract Background Immobility among intensive care patients can result in significant impairments. Reasons for this issue include a lack of specialised staff and equipment, as well as safety concerns associated with transferring patients to a therapy device. Nevertheless, early mobilisation is recognised as beneficial for improving patient outcomes. This study explores the perspectives of healthcare professionals on the use of a robotic system for patient mobilisation and identifies related stress and relief factors. Method This qualitative longitudinal study was conducted at a German university hospital, where 29 interviews were conducted with nurses at three different data collection points. The data were analysed using qualitative content analysis in accordance with Mayring. Findings The utilisation of the VEMOTION® robotic system generally did not lead to any physical discomfort. However, the adoption of this technology presented certain challenges. Non-routine users initially experienced psychological strain, primarily due to the extensive preparation required and the need to integrate the system into established routines. Additionally, structural factors, such as nurse-to-patient ratios and the layout of the care facilities, were identified as significant determinants affecting both the practicality of mobilisation and associated stress levels. Conclusions Robotic systems like VEMOTION® can alleviate the physical workload of nurses. Successful integration and psychological adaptation depend on familiarity and routine use of the technology. Addressing structural and staffing factors is crucial for optimising robotic assistance in patient care. Further research should delve into these dynamics and explore the broader implications of technology adoption in healthcare. Trial registration: clinicaltrials.org TRN: NCT05071248, Date: 2021/10/21 URL: https://clinicaltrials.gov/ct2/show/NCT05071248